Xala, ğalla, qālān: discussing medieval tax terms - Gor Margaryan (Banber Arevelagitut'yan Instituti, 2025)
The purpose of the study is to explore the origin and meaning of the term խալայ - xala, to identify the peculiarities of its application in the Armenian historical milieu, and to define at least approximately the chronological boundaries when the tax was in use in medieval Armenia. Xala became known mostly from epigraphic records of Armenia, where the term is mentioned in the immunity donations, in the instructions and references to the exemption of churches from tax obligations and from taxes, including xala. The paper will address all well-known explanations of the term, along with a comparative analysis with the Georgian historical environment, with the fiscal system of medieval Georgia, and, on the other hand, based on the analysis of source studies and definition of the etymology of the term and the phenomenon, a new definition of the term and answers to the above questions related to xala will be proposed as a hypothesis.